Nitrate supplementation and high-intensity cycling performance - Hoon, M. H.; Burke, L. B.; Jones, A. M.; Hopkins, W. G.; Johnson, N. J.; Halson, S. L.; Martin, D. T.; West, N. P.; Bartram, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Recent studies have demonstrated that consumption of inorganic nitrate enhances endurance performance, most likely via the conversion of nitrate to nitric oxide. Most of the research has been conducted on recreationally trained subjects, but in athletes cardiovascular adaptations to exercise training may blunt the response to nitric oxide. Aim To investigate the effect of nitrate supplementation in national-level cyclists on performance of two 4-minute cycling time trials, separated by 75 min. The effect of the timing of nitrate ingestion was also investigated. Methods: In a randomised cross-over design, 26 cyclists performed the time trials on Wattbike cycle ergometers under four conditions, each separated by a seven-day washout: consumption of 75 ml of nitrate-rich beetroot juice either 150 min or 75 min before the first time trial, consumption of a 30-ml top-up dose following the first time trial in the 150-min condition, and consumption of a placebo. Plasma nitrite was sampled at five time points. A linear mixed model with adjustments for learning effects and athlete fitness (peak incremental power) was used to estimate and express mean power in each time trial of each nitrate condition as percent change from that in the placebo condition, with probabilistic inferences based on a smallest effect of 1.0%. Results: Plasma nitrite concentration rose to a peak of ~50% above baseline by ~75 min after consumption of nitrate. Collectively, there was an unclear mean effect on average power in each of the nitrate conditions in the first time trial ( 1.1%, 90% confidence limits ±1.7%) and a possibly harmful effect on the second time trial (-0.5%, ±1.6%). For the fitter cyclists (+1SD), the effect of nitrate supplementation was possibly harmful in both time trials (-0.6%, ±2.8%; -1.7%, ±2.7%). Conclusion: On the basis of these results, acute nitrate supplementation in the form of beetroot juice cannot be recommended for high-intensity performance in highly trained cyclists.